Molecular variants of Grapevine rupestris stem pitting-associated virus infecting grapevines (Vitis spp.) in Brazil. - FAJARDO, T. V. M. (2017)
Grapevine rupestris stem pitting-associated virus (GRSPaV) is one of the most common viruses of grapevine. It is involved in the graft-transmissible disease rupestris stem pitting of the rugose wood complex. The objective of the research was to perform the molecular characterization of the coat protein (CP) gene of sixteen Brazilian GRSPaV isolates aiming to determine the occurrence of molecular variants (strains) of this virus. Nine grapevine samples were evaluated, from which dsRNA was extracted. Nucleotide sequences were generated by Next generation sequencing (NGS). Fifteen complete sequences of the GRSPaV CP gene were obtained and phylogenetically analyzed. Multiple alignments of the sequences showed identities of nucleotides ranging from 82% to 99%, suggesting high variability among the CPs of Brazilian isolates. The study revealed that genetic variability of GRSPaV comprising three molecular variants is also present in Brazilian grapevine genotypes.Key words: GRSPaV, Foveavirus, strains, lineages, genetic variability. O GRSPaV é um dos vírus mais comuns da videira. Está associado à doença transmissível por enxertia denominada caneluras de rupestris que compõe o complexo do lenho rugoso. O objetivo do trabalho foi realizar a caracterização molecular do gene da proteína capsidial (CP) de 16 isolados brasileiros de GRSPaV visando determinar a ocorrência de variantes moleculares desse vírus. Nove amostras de videira foram avaliadas das quais foi extraído dsRNA. As sequências de nucleotídeos foram geradas pelo sequenciamento de nova geração (NGS). Quinze sequências completas do gene CP de GRSPaV foram obtidas e filogeneticamente analisadas. Os alinhamentos múltiplos entre as sequências mostraram identidades de nucleotídeos variando de 82% a 99%, sugerindo alta variabilidade entre as CPs de isolados brasileiros. O estudo revelou que a variabilidade genética de GRSPaV compreendendo três variantes moleculares também está presente nos genótipos de videira no Brasil. Palavras-chave: GRSPaV, Foveavirus, estirpes, linhagens, variabilidade genética.